Applied thematic analysis - Guest, Greg, 1963-; MacQueen, Kathleen M.; Namey, Emily E. (Los Angeles : Sage Publications, 2012)
"This book provides step-by-step instructions on how to analyze text generated from in-depth interviews and focus groups - i.e., transcript s. The book is primarily designed for research studies with an applied focus, but is also useful for theoretically oriented qualitative resear ch. The book covers all aspects of the qualitative data analysis proces s including planning, data preparation, identification of themes, codeb ook development and code application, reliability and inter-coder agree ment, data reduction techniques, comparative techniques, integration wi th quantitative data, and software considerations. The book describes w hat the authors call "applied thematic analysis", because it is the app roach predominantly used in applied qualitative studies (and increasing ly in academic contexts). The method employs a phenomenological approac h to data analysis which has a primary aim of describing the experience s and perceptions of research participants. The approach presented is s imilar to Grounded Theory - in that it is inductive, content-driven, an d searches for themes within textual data - and is complementary to Gro unded Theory on many levels. However, within an applied context a pheno menological approach is primarily concerned with characterizing and sum marizing perceptions and lived experiences and applying the results to a particular research problem, rather than building and assessing theor etical models"--
Includes bibliographical references and indexes.
Keywords: Social sciences -- Research -- Methodology; Qualitative reasoning